WHEN SCANGUILT MEETS THE REALITY SHOW: ‘DOING-GOOD’ ENTERTAINMENT AND MEDIA REPRODUCTION OF COLONIAL IMAGINARY OF THE ‘SOUTH’ - Vićentić, Jelena (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2021)
This paper examines the humanitarian reality genre in Norway as a form of entertainment, education, and information. Norwegian ‘doing-good’ entertainment content is explored as representative of particular cultural and historical context, especially due to the popularity, frequency of broadcasting and the specific societal status assigned to this format. An overview and the consideration of the fundamental themes and elements of the genre elaborates on the concepts of ‘Scanguilt’ and ‘regime of goodness’, relevant for the interpretation of these programs. Differences in comparison to non-fiction journalistic storytelling are also pertinent. Drawing from Tvedt’s thesis on the strategic communication regime, the methods, actors and effects of this genre of entertainment, education and information are seen in a wider spectrum, not limited to the socio-political outcomes apparent only in the Norwegian context. This point of departure enables the move from the consequences to the Norwegian identity and society in the direction of the effects of the media reproduction of coloniality.
Keywords: doing-good reality show, strategic communication regime, Global South, othering, coloniality.